Rethinking manhood an interview with Ted Bunch. (New York, NY Columbia University, 2013)
“For Ted Bunch, gender-based violence and discrimination against women and girls are rooted in a history of male domination that has deeply influenced the definition of manhood in our culture. Bunch is the co-founder of A CALL TO MEN, a violence prevention organization that provides training and education for men, boys, and communities. Bunch has lectured in countries such as Israel, South Africa, Ghana, and Brazil, among others, and was appointed by UN Secretary General Ban Ki-moon as a Committee Member to UNiTE, an international network of male leaders working to end violence against women. In an interview with the Journal, Bunch discussed the concept of manhood and how social norms and culture have impacted the current notion of masculinity.”
Keywords: Bunch, Ted; Family violence; Intimate partner violence; Man-woman relationships; Masculinity; Men -- Identity; Patriarchy; Rape in the military; Sex discrimination against women; Sexism; Sexual harassment in the military; Women -- Violence against